2019
DOI: 10.1007/s42452-019-1120-1
|View full text |Cite
|
Sign up to set email alerts
|

Geometry optimization for structural reliability and performance of a thermoelectric generator

Abstract: The opposing requirements for the performance and reliability of a thermoelectric generator (TEG) are investigated with numerical finite element analysis simulations. The parameters that significantly influence the operational performance and structural reliability of a TEG are considered for simultaneous optimization. The design of experiments based response surface optimization methodology in conjunction with results from finite element analysis was employed to identify optimal parameters from the structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Numerous studies have already shown how the performance and of TEGs can be significantly increased by optimizing their geometry. [63][64][65] If temperature distribution of the presented TEG can be modeled adequately, this will prospectively allow an individual optimization. Figure 9 shows a comparison of the expected temperature distribution of an FEM simulation (Figure 9A) and the real temperature distribution measured by IR-Cam (Figure 9B) for steady state conditions under free convection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have already shown how the performance and of TEGs can be significantly increased by optimizing their geometry. [63][64][65] If temperature distribution of the presented TEG can be modeled adequately, this will prospectively allow an individual optimization. Figure 9 shows a comparison of the expected temperature distribution of an FEM simulation (Figure 9A) and the real temperature distribution measured by IR-Cam (Figure 9B) for steady state conditions under free convection.…”
Section: Resultsmentioning
confidence: 99%
“…The geometry of the modules determines the size of this gradient. Numerous studies have already shown how the performance and efficiency of TEGs can be significantly increased by optimizing their geometry 63–65 . If the temperature distribution of the presented TEG can be modeled adequately, this will prospectively allow an individual optimization.…”
Section: Resultsmentioning
confidence: 99%
“…New materials and production methods have been the focus of recent research for thermoelectric device improvement [20,21]. Others have studied what causes thermoelectric modules to degrade and fail, and they have provided solutions to these problems [22][23][24].…”
Section: Introductionmentioning
confidence: 99%